2008
DOI: 10.1089/ten.tea.2008.0215
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disc Tissue Engineering Using a Novel Hyaluronic Acid–Nanofibrous Scaffold (HANFS) Amalgam

Abstract: Degeneration of the intevertebral disc represents a significant musculoskeletal disease burden. Although spinal fusion has some efficacy in pain management, spine biomechanics is ultimately compromised. In addition, there is inherent limitation of hardware-based IVD replacement prostheses, which underscores the importance of biological approaches to disc repair. In this study, we have seeded multipotent, adult human mesenchymal stem cells (MSCs) into a novel biomaterial amalgam to develop a biphasic construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 62 publications
2
131
0
Order By: Relevance
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig. 15).…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig. 15).…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…In addition, the presence of the CP peptide sequence which is normally present in chondrocytes and plays an integral role in cartilage formation and Col-II binding may also have resulted in higher affinity of the cells toward Construct II. Col-I and Col-II are both present in fibrocartilage and therefore Construct I may be more suitable for TE of intervertebral disc space, while Construct II may be more apt for hyaline or elastic cartilage TE [114]. Thus, our results indicate that both constructs provided stable matrices for cell proliferation, adhesion and growth and that the adhesion of the cells depended largely on the peptide composition.…”
Section: Cell Morphology and Adhesionmentioning
confidence: 67%
“…Promising results have been reported 24 weeks after nucleotomy with additional intradiscal application of different HA formulations in monkeys [9]. Latest studies focused on cell-free disc implants and found promising results for HA-based biomaterials [10,11]. Cell-free implants made of polyglycolic acid (PGA) and HA induced the regeneration of articular cartilage in a sheep model [12].…”
Section: Introductionmentioning
confidence: 99%